2021
DOI: 10.14393/sn-v33-2021-57483
|View full text |Cite
|
Sign up to set email alerts
|

Microclimatic analysis of mangroves in two distinct categories of Protected Areas and conserved status

Abstract: Mangrove forests provide essential ecosystem services to human communities, including climate regulation. In Brazil, the National System of Nature Conservation Units divides Protected Areas (PAs) into two categories: Full Protection (FP) and Sustainable Use (SU). The FP areas are composed of five categories, including National Parks, and the SU areas comprise seven categories, such as Environmental Protection Areas. The current research compared climatic attributes, leaf area index, and vegetation structure de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Despite the region's conservation, studies have identified clearings in mangrove areas in the Iguape region due to the increase in invasive aquatic macrophytes in this sector that resulted from the opening of the Valo Grande canal [26]. In the northern section, microclimatic monitoring of mangroves has been occurring, with variations interpreted as an indicator of changes in mangrove structure at its edge and inside the ecosystem [27,28].…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the region's conservation, studies have identified clearings in mangrove areas in the Iguape region due to the increase in invasive aquatic macrophytes in this sector that resulted from the opening of the Valo Grande canal [26]. In the northern section, microclimatic monitoring of mangroves has been occurring, with variations interpreted as an indicator of changes in mangrove structure at its edge and inside the ecosystem [27,28].…”
Section: Study Areamentioning
confidence: 99%
“…The equipment was programmed to register every 10 min. The current event was recorded only at the station located in the northern sector of the coastal system [27,28].…”
Section: Climatementioning
confidence: 99%
See 1 more Smart Citation